Návrh marketingové strategie společnosti Hestego s. r. o. - Pala, Kateřina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Předmětem bakalářské práce „Návrh marketingové strategie společnosti Hestego s. r. o.“ je seznámení se současnou marketingovou strategií podniku a odvětvím, na kterém působí a následné navržení vhodných změn marketingové strategie. V první, teoretické části práce je obsažen obecný výklad marketingu spolu s hlavními metodami marketingových analýz. Druhá, praktická část je zaměřena na aplikaci této teorie a metod do praxe, analyzování současného vývoje okolí společnosti Hestego s. r. o., jejího vnitřního prostředí a navržení změn v marketingové strategii.

The aim of this bachelor assignment “The Proposal of marketing strategy of Hestego s. r. o.” is to familiarise readers with an actual marketing strategy of a company and its entrepreneurial environment and proposition of further and suitable changes in actual marketing strategy. In the first theoretical part is contained general interpretation of marketing together with the main methods of marketing analyses. The second practical part is aimed to put the theory and methods into practise, to analyse actual progress of corporate environment of Hestego s. r. o., its internal environment and to propose new marketing strategy.
The Proposal of Marketing Strategy of Hestego s. r. o.
Keywords: Marketing; marketingová analýza; marketingová strategie; marketingový mix; Marketing; marketing analysis; marketing strategy; marketing mix